Investigates The Implementation of Kinesthetic Intelligence-based Thematic Learning: A Case Study in Elementary School's Second-Grade - Sofian Gunawan; Muhammad Syifa; Dede Margo Irianto; Rendi Restiana Sukardi (CV. Dharma Samakta Edukhatulistiwa, 2023)
Kinesthetic intelligence-based thematic learning is a theme learning approach where learning activities entail more movement and physical activity (kinesthetic) using an active learning paradigm. The fact that each learner has a unique learning and information-capture potential serves as motivation for applying this knowledge. Therefore, it is crucial for teachers to present their lessons in unique and original ways so that students will readily accept them. Applying kinesthetic intelligence-based theme learning has a number of benefits, including making it simpler to directly explain subject to kids because learning includes students' physical abilities. This study aims to characterize learning, how learning is put into practice, and how thematic learning based on kinesthetic intelligence is evaluated in Baros Mandiri 3 Elementary School's second grade. A case study research design was chosen as the research methodology in this study. employing observation and interviewing as data collection methods. The findings of this study are recommendations for (1) kinesthetic intelligence-based learning planning, which comprises, and (2) kinesthetic intelligence-based theme learning implementation. (3) Kinesthetic intelligence class 2-based evaluation of thematic learning, which involves formative and daily evaluation.